Spectacle coverage for presbyopia correction and its associated factors among employees of an academic centre in Tehran - Fateme Alipour; Ramin Mehrdad; Parya Abdolalizadeh; Hamidreza Pouragha; Mehrdad Esmaili (Scientific Reports)
Abstract Near-vision is important for employees to reach better performance. The prevalence of uncorrected presbyopia ranges from less than 10–90% according to various sociodemographic factors including age, sex, educational level, affordability, and awareness. Current study aims to determine the prevalence of spectacle coverage for presbyopia correction and its associated factors among adult employees of a university. A cross-sectional study was conducted on Tehran University of Medical Sciences’ staffs aged ≥ 30 years in 2018–2019. All participants were assessed for distance and near visual acuities. Presbyopia was defined as inability to read 20/50 (N8) at 35 cm despite of corrected distance VA of at least 20/50 in the better eye. Total spectacle coverage for presbyopia was calculated as the number of participants with current near vision spectacle ⁄ number of participants with presbyopia. If persons with presbyopia had spectacles that allowed near vision to improve to 20/50 (N8) or better, it was true near spectacle coverage. Included was 4022 participants with mean (standard deviation) age of years 43.61 (7.92) years (range: 30–75 years). The prevalence of presbyopia was found to be 12.6% (507/4022). The total and true spectacle coverage for presbyopia correction were 35.9% (182/507) and 22.7% (115/507), respectively. Female (OR = 4.89, 95%CI = 1.82–13.18, P = 0.002), age ≥ 45 years (OR = 18.69, 95%CI = 1.69-206.18, P = 0.02), hyperopic refractive error (OR = 5.61, 95%CI = 1.75–17.93, P = 0.004), and poor to fair level of general health (OR = 2.94, 95%CI = 1.16–7.69, P = 0.02) were factors significantly associated with the total spectacle coverage. Academic educational level (OR = 2.76, 95%CI = 1.03–7.45, P = 0.04) and poor to fair general health (OR = 3.45, 95%CI = 1.41–8.33, P = 0.007) affected the true spectacle coverage. Nearly one-third of employees with presbyopia used spectacle for near vision, among whom 63% had true near spectacle. Near spectacle use was higher in elderly females with hyperopia and poor to fair general health. People with academic educational level and poor-fair general health wore true near spectacle.